FEM analysis of 3D lattice structures of ABS material - et.al, Seong-Gyu Cho (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
FDM is a typical additive manufacturing method. Since FDM is a method of stacking layers one by one, it generally has a flat lattice structure. In this study, by checking the distribution of stress and deformation for several lattice structures made of ABS material, it is intended to find a structure with better mechanical properties with less material. Several three-dimensional lattice structures are modeled using parametric modeling. Subsequently, a constant pressure is applied to the same area to check the stress and strain distribution. A structure with a low maximum stress value in the stress concentration region and a small amount of deformation will have the best mechanical properties. To do this, parametric modeling is performed using Inventor to model four three-dimensional lattice structures. Afterwards, use Ansys Workbench to check the stress and deformation distribution. Looking at the stress distribution, stress concentration occurred in the truss supporting the upper surface of the SC structure. In the BCC and PTC structures, stress concentration occurred at the point where the upper surface and the truss met. In the FCC structure, it can be seen that the load is distributed throughout the truss structure. Looking at the deformation distribution, both the SC and BCC structures show similar amounts of deformation. It was confirmed that the FCC structure had less maximum deformation than the PTC structure with the thickest truss. Unlike previous studies, it was confirmed that the higher the internal filling rate, the better the mechanical properties may not come out. The FDM method can obtain different mechanical properties depending on the internal lattice structure as well as the internal filling rate. In a later study, we will find a new calculation algorithm that applies variables by FDM characteristics using the data obtained by printing the actual specimen.